2019
DOI: 10.1016/j.atmosenv.2019.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering from volcanic-sand particles in deposited and aerosol form

Abstract: The light-scattering properties of volcanic sand collected in Iceland are studied here to characterize the sand particles and develop a reference for future remote-sensing observations. While such sand is common in Iceland, the smaller-size fraction can be readily transported by winds and found in the atmosphere at distant locations. The sand appears dark when deposited on a surface due to the high optical absorption of the material. Therefore, atmospheric regions containing such particles during a dust storm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The spectral reflectance estimated for the pure volcanic sand was about 0.03, which is very similar to a black body (0.0) (Dagsson-Waldhauserova, 2014;Peltoniemi et al, 2015). Zubko et al (2019) measured the complex refractive index of milled volcanic sand from the same area. The imaginary part of the complex refractive index (k), responsible for absorption, was 0.01 (λ = 647 nm), which is around one order of magnitude higher than the average values for natural dust from Sahel (0.002, λ = 660 nm), North Africa-Sahara and Easter Asia (0.001, λ = 660 nm) (Di Biagio et al, 2019).…”
Section: 5mentioning
confidence: 65%
See 1 more Smart Citation
“…The spectral reflectance estimated for the pure volcanic sand was about 0.03, which is very similar to a black body (0.0) (Dagsson-Waldhauserova, 2014;Peltoniemi et al, 2015). Zubko et al (2019) measured the complex refractive index of milled volcanic sand from the same area. The imaginary part of the complex refractive index (k), responsible for absorption, was 0.01 (λ = 647 nm), which is around one order of magnitude higher than the average values for natural dust from Sahel (0.002, λ = 660 nm), North Africa-Sahara and Easter Asia (0.001, λ = 660 nm) (Di Biagio et al, 2019).…”
Section: 5mentioning
confidence: 65%
“…The results showed that the volcanic sand from Iceland reduces the surface albedo and increases the melting rate of snow similarly to black carbon. Icelandic dust has strong absorption capacity (Zubko et al, 2019). Indeed, Icelandic dust is also rich in iron (Fe) (e.g., Arnalds et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Back-scattering from snow and regolith has been measured by (Piironen et al, 2000, Kaasalainen et al, 2002, Näränen et al, 2004, Kaasalainen et al, 2005, Kaasalainen et al, 2006. FGI has a large database of different measurements of bidirectional reflectance factors available that can be used for model validation: (Peltoniemi et al, 2007, Wilkman et al, 2016, Zubko et al, 2019, Peltoniemi et al, 2020, Xu et al, 2009. Another well-managed library is SPECCHIO by (Hueni et al, 2009), and in planetary field SSHADE (Schmitt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Extreme snow dust storms (Dagsson-Waldhauserova et al, 2015) can lead to insulation effect instead of snow melting (Dragosics et al, 2016;Möller et al, 2016) or to albedo decrease via a clumping mechanism, where small particles form larger particles in snow (Dagsson-Waldhauserova et al, 2015;Peltoniemi et al, 2015;Möller et al, 2019). Experiments have shown that volcanic dust (Iceland) can reduce albedo of snow similarly to BC (Peltoniemi et al, 2015;Zubko et al, 2019). Albedo changes on snow surface can also be caused by pigmented algae (Benning et al, 2014;Lutz et al, 2016), or cryoconite, a mixture of dust, pebbles, soot, and microbes (Di Mauro et al, 2017).…”
mentioning
confidence: 99%
“…Mineral dust is considered mainly a light-scattering particle in the atmosphere, but a light-absorbing particle when deposited on snow or ice [Intergovernmental Panel on Climate Change (IPCC), 2013]. Volcanic dust is, contrarily, a strongly absorbing particle with a spectral reflectance of 0.03 (Ovadnevaite et al, 2009;Peltoniemi et al, 2015;Zubko et al, 2019). In the Arctic, volcanic dust can reach altitudes of several kilometers and travel distances over 1,000 km (Arnalds et al, 2016;Dagsson-Waldhauserova et al, 2019).…”
mentioning
confidence: 99%